Computational models to explore the complexity of the epithelial to mesenchymal transition in cancer. (24th March 2020) - Cortesi, Marilisa; Liverani, Chiara; Mercatali, Laura; Ibrahim, Toni; Giordano, Emanuele
Abstract: Epithelial to mesenchymal transition (EMT) is a complex biological process that plays a key role in cancer progression and metastasis formation. Its activation results in epithelial cells losing adhesion and polarity and becoming capable of migrating from their site of origin. At this step the disease is generally considered incurable. As EMT execution involves several individual molecular components, connected by nontrivial relations, in vitro techniques are often inadequate to capture its complexity. Computational models can be used to complement experiments and provide additional knowledge difficult to build up in a wetlab. Indeed in silico analysis gives the user total control on the system, allowing to identify the contribution of each independent element. In the following, two kinds of approaches to the computational study of EMT will be presented. The first relies on signal transduction networks description and details how changes in gene expression could influence this process, both focusing on specific aspects of the EMT and providing a general frame for this phenomenon easily comparable with experimental data. The second integrates single cell and population level descriptions in a multiscale model that can be considered a more accurate representation of the EMT. The advantages and disadvantages of each approach will be highlighted, together with the importance of coupling computational and experimental results. Finally, the main challenges that need to be addressed to improve our knowledge of the role of EMT in the neoplastic disease and the scientific and translational value of computational models in this respect will be presented. This article is categorized under: Analytical and Computational Methods > Computational Methods Abstract : The combination of experimental and computational analysis is advancing the complete characterization of complex biological processes such as the epithelial to mesenchymal transition. Computational studies can be performed both in terms of signal transduction networks, that describe gene expression regulation and single cells or population dynamics, and multiscale models that integrate cell–cell and cell–environment interactions, besides modeling migration patterns.